Street child work in Latin American capitals (2006)
Objective. To identify the age, sex, mobility, education, work activity, working hours, street dwelling, and social security coverage in a group of children working in the streets in capital cities in Latin America. Material and Methods. Cross sectional study. A questionnaire was applied to 972 children working in the streets of Bogotá, Guatemala City, Mexico City, Quito and San Salvador. Results. A total of 63.3% subjects were boys; 39% were children from displaced families; 18% lived in the streets; 62% worked more than 40 hours per week; 19% were covered by the social security system, and 32% were street vendors. The behavior of variables differed significantly by city. Conclusion. Child labor in the streets is a dangerous activity characterized by long working hours and exposure to risk factors. Child work has different characteristics in each of the cities studied, which suggests that the solution to the problem must be designed on a case by case basis.